Constraining the nature of the possible extrasolar PDS110b ring system - Pinheiro, Tiago F. L. L. [UNESP]; Sfair, Rafael [UNESP] (EDP Sciences, 2021)
The young star PDS110 in the Ori OB1a association underwent two similar eclipses in 2008 and 2011, each of which lasted for a period of at least 25 days. One plausible explanation for these events is that the star was eclipsed by an unseen giant planet (named PDS110b) circled by a ring system that fills a large fraction of its Hill sphere. Through thousands of numerical simulations of the three-body problem, we constrain the mass and eccentricity of this planet as well the size and inclination of its ring, parameters that are not well determined by the observational data alone. We carried out a broad range of different configurations for the PDS110b ring system and ruled out all that did not match with the observations. The result shows that the ring system could be prograde or retrograde; the preferred solution is that the ring has an inclination lower than 60° and a radius between 0.1 and 0.2 au and that the planet is more massive than 35 MJup and has a low eccentricity (<0.05).
Keywords: Eclipses; Planets and satellites: dynamical evolution and stability; Planets and satellites: rings